PROPIONIC ACIDURIA IN A 5-MONTH-OLD CHILD - L. D. Fominykh; G. V. Solovyeva; M. L. Vyaznikova; N. G. Muratova; T. E. Serebrenikova; E. A. Kostyuchek (Union of pediatricians of Russia, 2014)
Propionic aciduria is a rare hereditary metabolic disease with autosomal-recessive inheritance mode associated with organic acid metabolic disorder. Early diagnostics is difficult as clinical symptoms caused by metabolic defects are often observed at hypoxicischemic central nervous system lesion, brain malformations and intrauterine infections. Laboratory examination reveals increased concentration of organic acids in blood and urine. The article presents observation of propionic aciduria in a 5-month-old child.